Screening For Potential Inhibitors Of Mycobacterium Tuberculosis Isocitrate Lyase: In Silico And In Vitro Approaches - Lee , Yie Vern (2017)

(untitled)
Tuberculosis (TB) that is caused by Mycobacterium tuberculosis (MTB) still remains as global epidemic and affects one-third of the world population, regardless of active TB or latent TB infection. The metabolism for active and latent MTB are different, for instance they have different energy generation cycle during active and latent stage. Instead of focusing on the drug targets during the active stage, which already have the effective therapeutic drugs, this study targeted isocitrate lyase (ICL), a potential target for dormant (latent) MTB energy generation cycle (glyoxylate cycle). Studies showed that without ICL, dormant MTB cannot survives within the lung of a murine model.